Nutritional modulation of intestinal drug-metabolizing cytochrome P450 by butyrate of different origin in chicken. (August 2017) - Kulcsár, Anna; Mátis, Gábor; Molnár, Andor; Petrilla, Janka; Wágner, László; Fébel, Hedvig; Husvéth, Ferenc; Dublecz, Károly; Neogrády, Zsuzsanna
Abstract: Intestinal cytochrome P450 (CYP) enzymes play key role in the first pass metabolism of orally ingested xenobiotics, providing a primary metabolic barrier, being of special importance in maintaining animal health and production. This study was aimed to investigate how intestinal drug-metabolizing CYPs can be modulated by nutritional factors in broiler chicken. We investigated the effects of the natural growth promoter ( n -)butyrate of different origin (feed supplementation of protected or non-protected forms and/or inducing caecal microbial production by supporting higher level of dietary non-starch polysaccharides [NSP]) on the activity of duodenal CYPs. To observe the connection between intestinal CYP activity and butyrate concentration, the distribution of differently originated butyrate was also assessed by measuring its concentration in various intestinal segments and different vessels of portal and systemic circulation. Butyrate of different origin showed varying distribution properties as being absorbed from different parts of the gastrointestinal tract. Intestinal CYP1A and CYP2H2 activities were increased by dietary butyrate supplementation and by the increased caecal microbial butyrate production, while CYP3A37 activity was minimally influenced by microbial butyrate only. The present study proved that both dietary and microbial butyrate could alter the activity of CYPs in the duodenal epithelium. Our findings suggest that intestinal CYPs could be induced not only by the intestinal luminal butyrate, but also from basolateral side, by the already absorbed butyrate. Such action of butyrate can be of special importance from food safety and pharmacotherapeutic point of view as it may modify the metabolism and intestinal kinetics of simultaneously applied xenobiotics. Highlights: Butyrate absorbed from different parts of the gut shows varying kinetic properties. Butyrate of different origin can influence the activity of intestinal CYP enzymes. Intestinal CYP enzymes could be induced from both the luminal and basolateral side.